Tinnitus-Related Changes in the Inferior Colliculus - Berger, Joel I.; Coomber, Ben (Frontiers in Neurology, 2015)
Tinnitus is highly complex, diverse, and difficult to treat, in part due to the fact that the underlying causes and mechanisms remain elusive. Tinnitus is generated within the auditory brain, however, consolidating our understanding of tinnitus pathophysiology is difficult due to the diversity of reported effects and the variety of implicated brain nuclei. Here, we focus on the inferior colliculus, a midbrain structure that integrates the vast majority of ascending auditory information and projects via the thalamus to the auditory cortex. The IC is also a point of convergence for corticofugal input and input originating outside the auditory pathway. We review the evidence, from both studies with human subjects and from animal models, for the contribution the inferior colliculus makes to tinnitus. Changes in the IC, caused by either noise exposure or drug administration, involve fundamental, heterogeneous alterations in the balance of excitation and inhibition. However, differences between hearing loss-induced pathology and tinnitus-related pathology are not well understood. Moreover, variability in tinnitus induction methodology has a significant impact on subsequent neural and behavioural changes, which could explain some of the seemingly contradictory data. Nonetheless, the inferior colliculus is likely involved in the generation and persistence of tinnitus perception.